2019
DOI: 10.1037/dev0000692
|View full text |Cite
|
Sign up to set email alerts
|

Can children prioritize more valuable information in working memory? An exploration into the effects of motivation and memory load.

Abstract: This is a repository copy of Can children prioritize more valuable information in working memory? An exploration into the effects of motivation and memory load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 62 publications
4
43
0
1
Order By: Relevance
“…Note that explicit reward was used in both studies to probe prioritization, thus the main difference is in the implementation of a compelling cover story that engages children in the task. Taken together, these findings support the idea that employing engaging and the age‐appropriate tasks is crucial (Atkinson et al, ; Light, Buckingham, & Robbins, ).…”
Section: Mnemonic Discrimination Developmentsupporting
confidence: 79%
See 1 more Smart Citation
“…Note that explicit reward was used in both studies to probe prioritization, thus the main difference is in the implementation of a compelling cover story that engages children in the task. Taken together, these findings support the idea that employing engaging and the age‐appropriate tasks is crucial (Atkinson et al, ; Light, Buckingham, & Robbins, ).…”
Section: Mnemonic Discrimination Developmentsupporting
confidence: 79%
“…It has been found that an age‐appropriate cover story may sufficiently motivate children in other cognitive domains. For examples, one study examined the impact of the use of reward with an age‐appropriate cover story (combatting an alien invasion) to motivate children aged 7–10 in a working memory task (Atkinson, Waterman, & Allen, ). Children showed higher accuracy for the valued items, suggesting that they are able to engage in executive control in order to prioritize high‐reward items when sufficiently motivated to do so.…”
Section: Mnemonic Discrimination Developmentmentioning
confidence: 99%
“…Note that explicit reward was used in both studies to probe prioritization, thus the main difference is in the implementation of a compelling cover story that engages children in the task. Taken together, these findings support the idea that employing engaging and the age-appropriate tasks is crucial (Atkinson et al, 2019;Light, Buckingham, & Robbins, 1979).…”
Section: Mnemonic Discrimination Developmentsupporting
confidence: 78%
“…It has been found that an age-appropriate cover story may sufficiently motivate children in other cognitive domains. For examples, one study examined the impact of the use of reward with an ageappropriate cover story (combatting an alien invasion) to motivate children aged 7-10 in a working memory task (Atkinson, Waterman, & Allen, 2019). Children showed higher accuracy for the valued items, suggesting that they are able to engage in executive control in order to prioritize high-reward items when sufficiently motivated to do so.…”
Section: Mnemonic Discrimination Developmentmentioning
confidence: 99%
“…Figure 7 illustrates the effect of cognitive load on the comparison between instructions emphasizing primacy or recency. We have also observed that children 7-10 years of age are able to prioritize within visual working memory, at least when sufficiently motivated to do so, though such effects appear to be somewhat smaller than those observed in adults (Atkinson, Waterman, & Allen, 2019).…”
Section: Prioritization Effectsmentioning
confidence: 57%